2021
DOI: 10.1111/pde.14714
|View full text |Cite
|
Sign up to set email alerts
|

The scope of health insurance coverage of vitiligo treatments in the United States: Implications for health care outcomes and disparities in children of color

Abstract: Background Patients of color are disproportionately impacted by vitiligo. Access to treatment depends greatly on insurance coverage. We, therefore, assessed current vitiligo treatment coverage policies across major United States health insurers to determine current patterns and coverage gaps for vitiligo. Methods The study surveyed 15 commercial health care insurers, 50 BlueCross BlueShield (BCBS) plans, Medicare, Medicaid, and Veterans Affairs. Information on treatment coverage for vitiligo, specifically pime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…1 In July 2022, ruxolitinib cream 1.5% was approved by the US Food and Drug Administration (FDA) for nonsegmental vitiligo in patients 12 years and older. 6,7 It is the only FDA-approved therapy for vitiligo. It is thought to work by inhibiting the Janus kinasesignal transducers and activators of the transcription pathway.…”
Section: Worth Notingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In July 2022, ruxolitinib cream 1.5% was approved by the US Food and Drug Administration (FDA) for nonsegmental vitiligo in patients 12 years and older. 6,7 It is the only FDA-approved therapy for vitiligo. It is thought to work by inhibiting the Janus kinasesignal transducers and activators of the transcription pathway.…”
Section: Worth Notingmentioning
confidence: 99%
“…There were 2 commonly cited reasons for denying coverage for therapies: vitiligo was considered cosmetic and therapies were not FDA approved. 7 In comparison, NB-UVB light phototherapy for psoriasis is not considered cosmetic and has a much higher insurance coverage rate. 9,10 The out-of-pocket cost for a patient to purchase their own NB-UVB light phototherapy is more than $5000.…”
Section: Health Disparity Highlightmentioning
confidence: 99%
“…1 In July 2022, ruxolitinib cream 1.5% was approved by the US Food and Drug Administration (FDA) for nonsegmental vitiligo in patients ages 12 years and older. 6,7 It is the only FDA-approved therapy for vitiligo. It is thought to work by inhibiting the Janus kinase-signal transducers and activators of the transcription pathway.…”
Section: Worth Notingmentioning
confidence: 99%
“…There were 2 commonly cited reasons for denying coverage for therapies: vitiligo was considered cosmetic and therapies were not FDA approved. 7 In comparison, NB-UVB light phototherapy for psoriasis is not considered cosmetic and has a much higher insurance coverage rate. 9,10 The out-of-pocket cost for a patient to purchase their own NB-UVB light phototherapy is more than $5000.…”
Section: Worth Notingmentioning
confidence: 99%
“…For instance, although vitiligo is associated with stigmatization and depression, particularly among racial and ethnic minority groups, 2 a 2021 cross-sectional evaluation of coverage for vitiligo treatments among more than 65 public and private payers found that 12% did not cover topical calcineurin inhibitors and over half did not cover phototherapy, with the most common reason for denial being that vitiligo is considered a cosmetic condition. 3 A recent analysis of claims data found that most patients with rosacea and melasma were unable to access first line treatments and that patients with melasma were 26-fold less likely to access treatments compared with those with rosacea. 4 Furthermore, treatments for inflammatory papules of rosacea (eg, topical metronidazole) are covered much more frequently than treatments for redness and flushing of rosacea (eg, topical brimonidine), even though flushing can cause burning and irritation that could be considered to reflect a disturbance of sensation.…”
mentioning
confidence: 99%